The Effect of Online Attendance, Performance Reporting Models and Additional Employee Income Allowance Schemes on Civil Servant Performance - Juhandi Juhandi; Hapzi Ali (Dinasti International Journal of Management Science, 2023)
The effect of online attendance, performance reporting models, and additional employee income allowance schemes on Civil Servant performance is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) Online attendance has an effect on civil servant performance. 2) The performance report model has an effect on civil servant performance; and 3) The additional employee income allowance scheme affects the performance of civil servants.